Effect of microstructural factors on the strength and deformability of ferrite-pearlite steels with different Mn and V contents [Mn 및 V 함량이 다른 페라이트-펄라이트 조직강의 강도와 변형능에 미치는 미세조직 인자의 영향] - Hong, T.-W.; Lee, S.-I.; Shim, J.-H.; Lee, J.; Lee, M.-G.; Hwang, B. (Korea Federation of Science and Technology, 2018)
This study examines the effect of microstructural factors on the strength and deformability of ferrite-pearlite steels. Six kinds of ferrite-pearlite steel specimens are fabricated with the addition of different amounst of Mn and V and with varying the isothermal transformation temperature. The Mn steel specimen with a highest Mn content has the highest pearlite volume fraction because Mn addition inhibits the formation of ferrite. The V steel specimen with a highest V content has the finest ferrite grain size and lowest pearlite volume fraction because a large amount of ferrite forms in fine austenite grain boundaries that are generated by the pinning effect of many VC precipitates. On the other hand, the room-temperature tensile test results show that the V steel specimen has a longer yield point elongation than other specimens due to the highest ferrite volume fraction. The V specimen has the highest yield strength because of a larger amount of VC precipitates and grain refinement strengthening, while the Mn specimen has the highest tensile strength because the highest pearlite volume fraction largely enhances work hardening. Furthermore, the tensile strength increases with a higher transformation temperature because increasing the precipitate fraction with a higher transformation temperature improves work hardening. The results reveal that an increasing transformation temperature decreases the yield ratio. Meanwhile, the yield ratio decreases with an increasing ferrite grain size because ferrite grain size refinement largely increases the yield strength. However, the uniform elongation shows no significant changes of the microstructural factors. ？ Materials Research Society of Korea.
Keywords: Deformation; Ferrite; Formability; Grain boundaries; Grain refinement; Grain size and shape; Pearlite; Pearlitic transformations; Steel; Steel research; Strain hardening; Tensile testing; Volume fraction; Yield stress; Austenite grain boundaries; Ferrite-pearlite; Grain refinement strengthening; Isothermal transformations; Microstructural factors; Strength; Transformation temperatures; Yield point elongations; Tensile strength